Efficacy and Safety of Atomoxetine Hydrochloride in Asian Adults With ADHD: A Multinational 10-Week Randomized Double-Blind Placebo-Controlled Asian Study. (January 2017) - Goto, Taro; Hirata, Yuko; Takita, Yasushi; Trzepacz, Paula T.; Allen, Albert J.; Song, Dong-Ho; Gau, Susan Shur-Fen; Ichikawa, Hironobu; Takahashi, Michihiro
Objective: The efficacy and safety of atomoxetine was assessed in adult ADHD patients from Japan, Korea, and Taiwan in this first placebo-controlled Asian clinical study in adults of an ADHD medication.Method: Atomoxetine was compared with placebo (195 atomoxetine, 196 placebo) over 10 weeks. The change from baseline to endpoint and changes over time in the Conners' Adult ADHD Rating Scale–Investigator Rated: Screening Version total score (CAARS-Inv: SV total score) were assessed along with changes in quality of life (QoL) and executive function.Results: Atomoxetine treatment resulted in a mean reduction of −14.3 (placebo, −8.8) in CAARS-Inv: SV total score and a steady increase of between-group differences from Week 2. Improvements in QoL and executive functioning were also observed. Treatment-emergent adverse events leading to discontinuation were infrequent (atomoxetine: 5.2%, placebo: 1.5%).Conclusion: Atomoxetine was tolerable and effective in improving QoL and executive function as well as ameliorating core ADHD symptoms in adult Asian patients.